Cerebrospinal fluid fistulas after iliosacral screw removal in post-traumatic pseudomeningocele - Valente, Angiola (Springer International Publishing, 2011)
Sacral fractures are rare but severe injuries. They are often associated with neurological impairment and pelvic instability. We present a case of a 28-year-old woman who sustained an H-type fracture of the sacrum with complete cauda equina syndrome treated with cauda equina decompression and pelvic percutaneous stabilization with an iliosacral screw. Two years after she underwent screw removal, but complained of back and nape pain after the operation. A lumbosacral MRI showed the presence of a lytic lesion involving the S1 and S2 bodies that was judged to be a pseudomeningocele leaning against the sacral screw hole and cerebrospinal fluid fistulas through this. To our knowledge, this is the first case of such a complication after sacral screw removal to be reported.